Unique ERα Cistromes Control Cell Type-Specific Gene Regulation - Krum, Susan A. (The Endocrine Society, 2008)
Estrogens play an important role in normal physiology and in a variety of pathological states involving diverse tissues including breast and bone. The mechanism by which estrogens exert cell type- and disease-specific effects, however, remains to be explained. We have compared the gene expression profile of the MCF7 breast cancer cell line with that of the osteoblast-like cell line U2OS-ERα by expression microarrays. We find that fewer than 10% of the 17β-estradiol (E2)-regulated genes are common to both cell types. We have validated this in primary calvarial osteoblasts. To dissect the mechanism underlying the cell type-specific E2 regulation of gene expression in MCF7 and U2OS-ERα cells, we compared the ERα binding sites on DNA in the two cell types by performing chromatin immunoprecipitation (ChIP) on genomic tiling arrays (ChIP-on-chip). Consistent with the distinct patterns of E2-regulated gene expression in these two cell lines, we find that the vast majority of ERα binding sites are also cell type specific and correlate both in position and number with cell type-specific gene regulation. Interestingly, although the forkhead factor FoxA1 plays a critical role in defining the ERα cistrome in MCF7 cells, it is not expressed in U2OS-ERα cells, and forkhead motifs are not enriched in the ERα cistrome in these cells. Finally, the ERα cistromes are correlated with cell type-specific epigenetic histone modifications. These results support a model for the cell type-specific action of E2 being driven primarily through specific ERα occupancy of epigenetically marked cis-regulatory regions of target genes.